Development of cooked, chilled, irradiated, vacuum-packed pancit bihon - Borras, Alyssa Erika L.
The feasibility of developing a cooked, chilled, irradiated, vacuum-packed Pancit bihon was undertaken to provide an alternative prepared meal that is microbiologically safe and with long shelf life. Cold processing by the application of irradiation eliminate disease causing microorganisms with no effect on food quality since heat was not applied to the food. The optimum irradiation dose that will inhibit microbial growth while ensuring the highest acceptability in sensory evaluation was determined by exposing vacuum-packed cooked Pancit bihon at irradiation doses of 1.0, 3.0 and 5.0 kGy and storing at chilled conditions. The extent of the effects of gamma irradiation was also determined by conducting a shelf-life study. Results show that an irradiation dose as high as 5.0 kGy can limit the growth of microorganism while maintaining acceptable sensory attributes including appearance, aroma, flavor, bihon texture and overall acceptability. It was found during the shelf-life study that irradiation was able to neutralize the retrogradation of bihon even at chilled conditions where acceptability scores > 6 was obtained even after 18 days of chilled storage. The shelf-life of Pancit bihon was also extended up to one month under good refrigeration conditions. The utilization of gamma irradiation in cooked- chilled products will enable food manufacturers provide consumers with convenience food products with increased safety and quality.